Energy-saving mechanism of series–parallel hybrid transmissions — A dynamic programming method based on matrix operations - Zhao, Junwei; Xu, Xiangyang; Li, Kaifeng; Guo, Wei; Liu, Yiqiang; Qian, Pengfei; Dong, Peng (Energy conversion and management, 2024)
The economic evaluation of hybrid transmission is a complicated numerical calculation problem in the finite time domain. Currently, employing traditional dynamic programming methods to evaluate a single design scheme consumes a lot of time, making it arduous to effectively compare performance disparities across various design schemes. This paper introduces a dynamic programming method based on matrix operations, enabling the determination of maximum energy-saving potential in hybrid transmission while reducing the evaluation time for a single design scheme from hours to less than 10 s. It unifies the design variables, constraints, and optimization objectives for multi-gear and multi-mode series–parallel hybrid transmissions (MGMM-SPHTs) during economic evaluation. By solving the performance of tens of thousands of design schemes, it is found that increasing the number of engine direct drive gears from 1 to 2 enhances the economy and power performance of series–parallel hybrid transmissions. For the optimal design scheme of Type-B vehicles, this enhancement results in a 1.712% increase in energy-saving efficiency and a 30.5% increment in power performance. Furthermore, this paper elucidates the adaptive relationship between MGMM-SPHTs and different vehicle types, revealing the energy-saving mechanisms under varied design schemes. This paper holds the promise of offering theoretical underpinnings and methodological instruments for selecting technical routes and optimizing design parameters for MGMM-SPHTs. [Display omitted] •A dynamic programming method utilizing matrix operations is proposed.•A comprehensive performance evaluation framework for MGMM-SPHTs is designed.•Swift economic evaluations of MGMM-SPHTs across extensive design variations are achieved.•The energy-saving mechanism inherent in MGMM-SPHTs is uncovered.